Keruntuhan Progresif Gedung Struktur Beraturan Dan Tidak Beraturan - Ardian Yolanda; Zulfikar Djauhari; Ridwan Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research aimed to examine the progressive collapse of regular and irregular structural building. This research conducted by analyzing the structural elements that were first destroyed due to addition of gravity load and lateral load of the earthquake. This analysis conducted by removing one or more critical columns with General Services Administration (GSA) guide. Examination of structural strength using finite element software based Demand Capacity Ratio (DCR) value. The regular structure will have progressive collapse if the DCR>2 and irregular structure will have progressive collapse if the DCR>1,5. Progressive collapse occurs when removal of five critical columns on the side of the regular structure, with the largest of DCR value is 4,665. In irregular structure, progressive collapse occurs when removal of four critical columns in middle of horizontal side of structure with the largest of DCR value is 3,44375. The analysis results show progressive collapse did not occurs when removal of single column from GSA guide. Progressive collapse only occurs after removal of some critical columns in pushover analysis results. This show that the structure is still capable to carrying the load when remove single column, but the structure is unable to carrying the load when some critical column were removed. Based on the deformation, the regular and irregular structures analyzed have progressive collapse of domino type. The value of robustness indicator is almost equal one, that indicated the load distribution is normal despite of the damage structure.Keywords : Progressive collapse, irregular structure, regular structure, GSA, DCR